Financial Development, Financial Constraints, and the Volatility of Industrial Output - Borja Larrain (Federal Reserve Bank of Boston, 2004)
More financially developed countries show lower volatility of industrial output. Volatility is particularly reduced in industries that are more financially dependent. Most of the reduction is in idiosyncratic volatility. Systematic volatility is reduced less strongly, implying that industries are more closely correlated with GDP in more financially developed countries. At the firm level, short-term debt is negatively correlated with output as financial development increases, suggesting that debt is used in a countercyclical way to stabilize production. The results indicate that financial development relaxes financial constraints mainly to smooth negative cashflow shocks.
Keywords: O16; G31; E32; G0; 330; financial development; financial constraints; volatility; Industrielle Produktion; Volatilität; Finanzmarkt; Finanzsektor; Vergleich; Welt